Enhancing Current Density and Specific Capacitance through Tensile TEMPO, Bacterial Cellulose and Polypirrole Nanocomposites - Yunus, Syukri; Manurung, Muhammad Fajar Ruhud; Aulia, Aulia; Arief, Yanuar Zulardiansyah (Andalasian International Journal of Applied Science, Engineering and Technology, 2024)
The researchers developed a bio-composite film material that serves as a substitute for metal. The materials used are TEMPO ((2,2,6,6-tetramethylpiperidine-1-oxyl)), Bacterial Cellulose, and Polypyrrole (Ppy). This research aimed to increase the material's current density and specific capacitance values using the drawing method. Composite nanomaterials are made by oxidizing BC (Bacterial Cellulose) with TEMPO. The resulting TOBC (TEMPO Bacterial Cellulose) material was mixed with Ppy using the in situ method. The mixture is then drawn wet—measurement of current density and capacitance using Cyclic Voltammetry (CV) Testing. The current density and specific capacitance results increased by 542.74% and 754.79% after drawing the nanocomposite material. It is directly proportional to the effects of characteristic testing, which includes SEM, XRD, and FTIR. As a result of the withdrawal of the polypyrrole, it will be more evenly distributed in the composite material, absorbing and coating the nata de coco. The researchers concluded that when the TOBC/Ppy fibers are straighter and denser, they achieve higher current density and capacitance values.